Accuracy of death certificate diagnosis of amyotrophic lateral sclerosis. - Chiò, A (1992)
STUDY OBJECTIVE--The aim was to determine the reliability of official mortality statistics in estimating long term trends of amyotrophic lateral sclerosis (ALS) in Italy. DESIGN--The study was a mortality follow up of cases of ALS. SETTING--Piedmond Region, northern Italy. SUBJECTS--Cases of ALS were identified from multiple sources between 1966 and 1985. MAIN RESULTS--Cause of death was determined for the cases who died between 1970 and 1985. Death certificates were obtained in 488 out of 510 cases (95.7%). ALS was mentioned in 365 (74.8%) of cases. The most frequent erroneous diagnoses were multiple sclerosis and malignant tumours. Demographic variables, such as sex, age at death, province of death, and calendar year of death, did not influence the percentage of true positive cases significantly. CONCLUSIONS--The death certificate diagnosis of ALS appears to be adequate for use in descriptive and analytical epidemiology.